Composition of Fatty Acids and Squalene Content of Wild Spinach (Amaranthus dubius Mart) Seed Oil - Soetjipto, Hartati; Krisdayanti, Mitra; Aminu, November Rianto (UI Scholars Hub, 2021)
This study aims to determine the yield of wild spinach seed oil obtained by continuous extraction methods using Soxhlet apparatus for 10.5 hours in n-hexane solvent, the physio-chemical properties, and the composition of wild spinach seed oil using the Gas Chromatography-Mass Spectrometry (GC-MS) method. Refinement of wild spinach seed oil was done by degumming and neutralization. The yield of wild spinach seed oil extraction before refinement was 4.36 ± 0.29% (w/w) while after refinement was 0.68 ± 0.033% (w/w). Physio-chemical properties of wild spinach seed oil after refinement was as follows: water content 0.37%; peroxide value 9.5 meq/kg; acid value of 0.53 mg KOH/g oil; saponification value 208.9 mg KOH/g oil. The results of GC-MS analysis showed that the wild spinach seeds were composed of 5 main components: dodecanoic acid (0.28%); tetradecanoic acid (0.08%); palmitic acid (1.31%); squalene (94.9%); and linoleic acid (3.34%).